Proceedings of a general court martial, held at Fort Royal, in the Island of Martinico, on the 6th and continued by adjourments to the 14th of April, 1762 upon the tryal of Major Commandant Colin Campbell (British trials, 1660-1900 ;, 1763)
Court martial trial of Major Commandant Colin Campbell for the murder of John McKaarg.